1979
DOI: 10.1128/aem.37.2.198-201.1979
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility of Rainbow Trout to Infectious Hematopoietic Necrosis Virus After Exposure to Copper

Abstract: Exposure of rainbow trout to sublethal levels of copper in water increased their susceptibility to infectious hematopoietic necrosis virus. In most instances, the percent mortality was twice as great in the stressed groups compared with those groups which were not stressed but received the same virus dose. Although the level of copper in the water influenced the mortality rates, the length of exposure did not prove to be critical, as similar results were obtained after 1, 3, 5, 7, or 9 days of exposure. When d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 8 publications
4
24
0
Order By: Relevance
“…The presenee of Cu"^ before and after infeetion increased zebrafish susceptibility to listeriosis. Similar results have been obtained by other authors, who reported that some teleosts demonstrate an increased susceptibility to bacterial diseases (Baker & Knittel 1983) or to viral infeetion (Hetrick, Knittel & Fryer 1979) after copper treatment.…”
supporting
confidence: 91%
“…The presenee of Cu"^ before and after infeetion increased zebrafish susceptibility to listeriosis. Similar results have been obtained by other authors, who reported that some teleosts demonstrate an increased susceptibility to bacterial diseases (Baker & Knittel 1983) or to viral infeetion (Hetrick, Knittel & Fryer 1979) after copper treatment.…”
supporting
confidence: 91%
“…The mechanisms involved in this response to cortisol elevation require further examination. Deleterious changes in the environment are associated with the outbreak of disease (Pippy & Hare, 1969;Giussani et al, 1976;Rodsaether et al, 1977;Brown et al, 1979;Hetrick et al, 1979;Knittel, 1981;Ewing et al, 1982) and both acute and chronic stresses have been shown to depress the number of circulating lymphocytes in teleost fish (McLeay, 1975a;Peters et al, 1980;Tomasso et al, 1983). With acute stresses this effect has been shown to be mediated by elevated cortisol levels (Pickering, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged elevation of blood cortisol levels has been shown to predispose some species of salmonid fish to infectious diseases (Pickering & Duston, 1983;Pickering & Pottinger, 1985;Woo et al, 1987), an effect almost certainly mediated by the suppressive action of corticosteroids on the fish's defence systems (Anderson et al, 1982;MacArthur et al, 1984;Grimm, 1985;Maule et al, 1987). There is now an accumulating body of evidence linking various forms of stress to a subsequent increase in the susceptibility of fish to a wide range of infectious diseases (Johansson & Bergstrom, 1977;Hetrick et al, 1979;Hanson & Grizzle, 1985; see also Wedemeyer & McLeay, 1981) and we believe that elevated cortisol levels play a major role in this phenomenon. In general, rainbow trout are more amenable than brown trout to aquaculture conditions and, in our experience, show fewer problems of stress-related diseases.…”
Section: Introductionmentioning
confidence: 90%